The new way of educating - Painter, Carrie Vashti (My University, 1899)
Introduction: The one thing needed is education. Let the people be educated! Let the people be educated! Was the hue and cry set up by Luther while he stood before the public, defying the Pope and burning the Papal Bulls and issuing his theses right and left. He pressed the button, as it were, that opened up to the world the modern education, with its various scenes. With the application of his compulsory educational system in the little district of Wittenberg, was kindled the flame that within these three hundred years, has spread all over the world, growing brighter with each succeeding year, and with plenty of light and speed to carry it down to the end of time, with the assurance that it will reach the brightness of eternal day.
Citation: Painter, Carrie Vashti. The new way of educating. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Historical Origin of Eduction; Pioneers of the System; Character of the System; Theses; Manuscripts (documents)